Diaphragm-protective mechanical ventilation. Issue 1 (February 2019) - Schepens, Tom; Dres, Martin; Heunks, Leo; Goligher, Ewan C.
Abstract : Purpose of review: Diaphragm dysfunction is common in mechanically ventilated patients and predisposes them to prolonged ventilator dependence and poor clinical outcomes. Mechanical ventilation is a major cause of diaphragm dysfunction in these patients, raising the possibility that diaphragm dysfunction might be prevented if mechanical ventilation can be optimized to avoid diaphragm injury – a concept referred to as diaphragm-protective ventilation. This review surveys the evidence supporting the concept of diaphragm-protective ventilation and introduces potential routes and challenges to pursuing this strategy. Recent findings: Mechanical ventilation can cause diaphragm injury (myotrauma) by a variety of mechanisms. An understanding of these various mechanisms raises the possibility of a new approach to ventilatory management, a diaphragm-protective ventilation strategy. Deranged inspiratory effort is the main mediator of diaphragmatic myotrauma; titrating ventilation to maintain an optimal level of inspiratory effort may help to limit diaphragm dysfunction and accelerate liberation of mechanical ventilation. Summary: Mechanical ventilation can cause diaphragm injury and weakness. A novel diaphragm-protective ventilation strategy, avoiding the harmful effects of both excessive and insufficient inspiratory effort, has the potential to substantially improve outcomes for patients.